(untitled) (Journal of Social Sciences Review, 2023)
The status of collection development in public libraries depicts the poor condition in the following four aspects: books, periodicals, rare material and digital information resources. The library staff mostly used the traditional sources as a tool for collection development i.e. Suggestion box Catalogues, Bibliographies, Book sellers/ publishers lists, Reviews of books and Journals. The existing collection development policies were not comprehensive, did not cover necessary aspects concerning to collection development. The public libraries were facing many obstacles and challenges in proceeding collection development process i.e. shortage of staff, insufficient financial resources, lack of training opportunities for library staff to update their professional skills, non-provision of internet connection and digital equipment to use the latest information communication technology, lack of funds for libraries collection development, Indifferent and neglecting attitude of the higher authorities towards libraries were burning issues and challenges to maintain the international standards of collection development within the public libraries of Punjab, Pakistan.